Poder local y participación ciudadana: la experiencia del presupuesto participativo en Villa El Salvador - Rojas Rojas, Rolando (2006)
This work is a study of case about the participative budget (PB) in the «limeño» district of Villa El Salvador. The PB is an instrument of local administration, by which a part of the municipal budget (10%) is decided in assemblies of local leaders. The interesting of the case of Villa El Salvador is that, as Limatambo (Cusco), this form of administration local was born as initiative of authority, several years before parliament made it in law (2003). The central point of this investigation consists in offering an evaluation of this experience in the context of the conflicts by local power.